(untitled) (Asian Journal of Social Science Studies, 2025)
Community Health Workers (CHWs) play a crucial role in providing essential healthcare services to communities in Bangladesh, forming a vital part of the healthcare system. However, ensuring community awareness about health is imperative, with a primary focus on empowerment. This necessitates engaging all stakeholders in health information literacy (HIL) through education and awareness efforts. In these contexts, health information professionals (HIPs) have the opportunity to collaborate with CHWs to strengthen community empowerment. This study explores potential areas where HIPs can collaborate with CHWs to help individuals find accurate health information related to primary and pre-secondary healthcare issues. Employing a case study approach, the research provides an in-depth observation and analysis of the potential collaboration between these two professional groups. Additionally, a survey method was incorporated to gather insights. Findings suggest that HIPs can play various collaborative roles, including instructor, marketer, motivator, awareness builder, and counselor. These roles highlight the potential for HIPs to contribute to enhancing health awareness and literacy within the community.